Exploring the Influence of Self-Regulated Learning, Instructor Support, and Campus Climate on Maritime Competence: Examining the Moderating Role of Psychological Well-Being - M. Farid Fauzi; Bayu Yudho Baskoro; Akbar Alim; Syafni Yelvi Siska; Fauziah Roselia (CV. Creative Tugu Pena, 2026)
This study aimed to examine the effects of self-regulated learning, instructor support, and campus climate on maritime competence among maritime cadets, with psychological well-being as a moderating variable. The study employed a quantitative explanatory research design. The population consisted of 670 students from Cohorts VII, VIII, IX, and X at Politeknik Pelayaran Sumatera Barat, Indonesia. A pilot test was conducted with 100 cadets, while the main study involved 570 respondents. Data were collected using a five-point Likert-scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 3. The findings revealed that instructor support had a positive and significant effect on maritime competence. In contrast, self-regulated learning, campus climate, and psychological well-being did not have significant direct effects on maritime competence. Furthermore, psychological well-being did not moderate the relationships between self-regulated learning, instructor support, campus climate, and maritime competence. These findings indicate that instructor support is the most influential factor in enhancing cadets' maritime competence within maritime vocational higher education. This study contributes theoretically by extending the understanding of maritime competence through the integration of individual, instructional, environmental, and psychological factors into a single structural model. Practically, the findings provide valuable insights for maritime higher education institutions to strengthen instructor competence and instructional quality in order to improve maritime competence among cadets.